The effects of cage on endplate collapse after stand-alone OLIF: based on finite element analysis and in vitro mechanics experiments - Li, Hao; Liu, Jiarui; Cui, Huifei; Shen, Nana; Wu, Futong; Zhang, Zhihao; Zhu, Zhongze; Qiu, Chensheng; Xiang, Hongfei (Frontiers in Bioengineering and Biotechnology, 2024)
Background: Lumbar degenerative diseases are an important factor in disability worldwide, and they are also common among the elderly population.Stand-Alone Oblique Lumbar Interbody Fusion (Stand-Alone OLIF) is a novel surgical approach for treating lumbar degenerative diseases. However, long-term follow-up after surgery has revealed the risk of endplate collapse associated with Stand-Alone OLIF procedures.This study aimed to investigate the effect of the cage factor on endplate collapse after Stand-Alone OLIF.Methods: Finite element(FE) models and calf lumbar functional units were established separately and used to simulate Stand-Alone OLIF surgery.On the L5 endplate of the FE model and the calf lumbar functional unit, 12 cage positions from anterior to posterior, 16 cage inclination angles from 0°to 15°, and 4 cage heights were selected to simulate surgical models with different cage positions.Compression loads of 400N were applied to the upper surface of the superior vertebral body of the cage, and 10Nm torques in four directions were used to simulate four different physiological movements of the lumbar spine: flexion, extension, lateral curvature and torsion, in order to compare the range of motion of the surgical segment and the endplate stress.Results: When the cage is placed closer to the anterior and posterior edges of the endplate and when the height of the cage exceeds 12mm, the intervertebral range of motion at the surgical segment is greater and the stress on the endplate is higher during various lumbar spine activities.When the cage is inclined at an angle within 15°, there are no significant differences in the corresponding endplate stress and the range of motion.For Stand-Alone OLIF surgery, inserting the cage in the central anterior-posterior position of the intervertebral space and selecting a cage with a height not exceeding 12mm can reduce the stress on the endplate after surgery, which is more conducive to the stability of the lumbar spine postoperatively and reduces the risk of postoperative endplate collapse. The inclination angle of the cage placement does not significantly affect postoperative endplate stress or lumbar stability.